Sign Analysis in Room Movie Script - Wahyu Adnyani (ELITE: Journal of English Language and Literature, 2016)
This research employs the qualitative method in analyzing the object of the research. The data source was acquired from the movie written by Emma Donoghue 2014, and the secondary data in this research is acquired from script data in the Room novel by Emma Donoghue 2010. The source of data in this study comes from The Room Movie Script. The data collection technique used by the researcher is Searching and downloading, Reading, Identifying, Classifying, and coding Then the researcher performed data analysis techniques by Presenting the data, Describing the data, Analysis of the data, and Concluding. The researcher found 19 signs that come from Ma and Jack in this movie script. The findings revealed that two kinds of signs were found in the Room movie script including Signifier and Signified. In common signifier means a literary word where as signified means another meaning from a signifier that has more detail and a deep sign explanation. The Room movie script is represented many messages to the audience through its signs, especially for the reader. The researcher hopes the reader can understand every single meaning in this movie script, due reader can distinguish and easy to get the true meaning also it can be a source of research or guidance to act for daily life. Keywords: Room movie script, Sign, Signifier, Signified Â